VIth World Congress on Science and Football, Book of Abstracts, January 16-20, 2007, Antalya, Turkey - Poster Presentations - Females and Football (Journal of Sports Science & Medicine, 2007)
Summaries on the following topics: P-105 Sports injuries in woman soccer players P-106 Countermovement jumping genre differences in soccer P-107 Sleep, pre-game fatigue, and game performance in female college soccer players P-108 Game characteristics of Asian Women`s Rugby P-109 Effects of pre-cooling and warm-up intensity on soccer-specific intermittent exercise performance in heat P-110 Physical status of elite female soccer players P-111 Iron status in elite female soccer players